Prooxidant-antioxidant processes in blood and liver of murine rodents (Myodes glareolus and Apodemus flavicollis) under single irradiation - Yu. P. Hrynevych; L. I. Makovetska; A. I. Lуpska; O. O. Burdo (Ядерна фізика та енергетика)
The effect of total single X-ray irradiation (1.5 Gy) on the course of free radical processes (FRP) in the blood and liver of red fistula (Myodes glareolus) and yellow-throated mouse (Apodemus flavicollis) was studied. It is shown that physicochemical regulation of FRP in the blood of murine rodents under total X-ray irradiation (1.5 Gy) in the early stages is carried out mainly due to catalase and reduced glutathione (GSH). This is evidenced by the stoichiometry of the CL reaction and symbat changes in the prooxidant-antioxidant ratio (PAR) and basic kinetic parameters of the CL reaction (Imax, Ifin) and antibat changes to PAR - catalase and GSH.